REKRUTMEN PARTAI AMANAT NASIONAL SEBAGAI PARTAI PENGUSUNG, DALAM PEMENANGAN ISTRI BUPATI BUTON DI DPRD KABUPATEN BUTON PERIODE 2014-2019 - Yasni, Andi; Saad, Muhammad; A. Kambo, Gustiana (Universitas Hasanuddin, 2021)
This study aims to explain and analyze how the Partai Amanat Rakyat (National Mandate Party (PAN) recruitment process as the bearer party, in winning the wife of the Regent of Buton in the Buton Regency DPRD 2014-2019 period. The type of research used is descriptive qualitative which describes the subject and object of research based on empirical facts. The data source used was the chairman of the Buton Regency PAN, the success team, party cadres, documents and archives. Data were collected through the interview method. In this research, it is produced that there is political recruitment that is not transparent. Based on the opinion of some experts, PAN does not use an open recruitment method but instead uses a closed recruitment method. In this case, Lis Elianti has no experience in politics. Lis Elianti is a housewife with final education.